Tradisi A’rera’ pada Masyarakat Petani di Desa Datara Kecamatan Tompobulu Kabupaten Gowa (Suatu Tinjauan Sosial Budaya) - Rasyid, Soraya (Rihlah: Jurnal Sejarah dan Kebudayaan, 2014)
A’rera tradition ’ for Village Community Datara Tompobulu District of Gowa implemented with the advanced preparation in advance as set the correct time, prepare supplies such as tools required during the event. Furthermore a’rera executed alternately with each other. This means that each participant or person engaged in activities that a’rera turn to assisted working the fields or gardens. This rule was made not in writing but based on agreement among participants a’rera musawarah. From a social point of view of culture, tradition a’rera ’ can change the structure of society in the new forms, eventually evolved tarap their lives for being able to cultivate the land and paddy plantation they become productive. In addition, the social impact they caused on increasing their agricultural productivity through a’rera tradition is increasing joints life better than ever before. A’rera indirectly give the feel of a very conducive life because through a’rera means’ they can help each other and feel the social dimension within each petani.Tujuan implementation a’rera tradition’ for rural communities Datara Tompobulu District of Gowa aims to to facilitate the implementation of agricultural work, finish work in the garden to the maximum, foster a sense of brotherhood and mutual help instill among fellow farmers and residents in the village Datara. A’rera tradition should be preserved and developed in order to maintain the erosion of local heritage because it genitas this legacy is a legacy that is capable members positive color in building lifestyle of the farming community in particular and society in general Indonesia.